ANÁLISE DO EIXO TEMÁTICO GESTÃO EDUCACIONAL DO PLANO DE AÇÕES ARTICULADAS NO NORDESTE DO BRASIL - Sthenio José Ferraz Magalhães; Verônica Soares Fernandes (Universidade do Oeste de Santa Catarina, 2012)
Using an approach of qualitative-quantitative nature, this study aimed to analyzethe main theme of the Educational Management in Plan of Articulated Actions(PAA), in order to understand how to configure the democratic management in thecontext of small cities located in the Northeast of Brazil. Guided by the perspectiveof documentary research, we used data collection method for the analysis ofofficial documents of the Federal Government and the database of the PAA ofthe municipalities in the sample that had lower in the Index of Basic Educationin 2005 and 2007. Based on the indicators defined later, the results suggest thatthe mechanisms that facilitate democratic management are weakened in the citiessurveyed. Spaces municipal participatory planning, such as the Municipal Council of Education and the Municipal Education Plan, do not exist or are disjointed. At school, the instances of democratic experiences, such as the School Board, the formulation of the pedagogical project and the election of directors, are negligible and far to express the desires locations. Thus, we infer that there may be a relationship between instances of the failure of democratic management and facilitating low Indexes of Basic Education these municipalities, establishing a logical connection between the elements of democratic management and quality of education.